The right to health: discriminatory treatment against migrant workers in Malaysia - Muhammad Faliq Abd Razak; Rohaida Nordin (Penerbit Universiti Kebangsaan Malaysia, 2018)
Due to globalization, migration has become a worldwide trend, and now poses a new challenge to countries that receive and send migrant workers. Many issues have arisen from this trend, especially in terms of the rights of the migrant workers. Malaysia is one those countries that receive migrant workers, with 6.7 million migrants working in Malaysia, comprises of both with legal and illegal status. Without a doubt, Malaysia is a receiving country which depends a lot on migrant workers in boosting her productivity, especially in the economic and development sectors. Migrant workers in Malaysia are required to be covered by a health insurance scheme, particularly for compensation in the event of an accident. The question is whether the right of migrant workers to access healthcare in Malaysia is protected adequately without burdening the government, particularly in terms of the cost? Has the practice in Malaysia fulfil the right to health of migrant workers? Therefore, this article aims at analysing the laws and related instruments governing the issue of right to health of migrant workers in Malaysia. The methodology used theoretical analysis and interviews of identified target groups in order to obtain the primary. The interim analysis demonstrates that the existing policies and legal framework in Malaysia are practising discriminatory treatment against migrant workers in terms of access to healthcare and social benefits.